Integrating Public Policy for Sustainable Tourism Development in Badung Regency, Bali: Enhancing Spirituality, Social Harmony, and Environmental Stewardship - Elsa Herlina, Putu; Diah Utari Dewi, Nyoman; Putu Sri Widnyani, Ida Ayu; Hanafiah, Mohd Hafiz (Indonesian Association for Public Administration (IAPA), 2025)
This study aims to explore the challenges and potential solutions in advancing sustainable tourism in Badung Regency, Bali Province, with a particular focus on three core elements: spirituality (Parhyangan), social relations (Pawongan), and environmental sustainability (Palemahan). As tourist numbers continue to rise, issues such as a lack of respect for sacred sites, social tensions between visitors and local communities, and negative ecological impacts have become increasingly urgent. Employing a qualitative methodology—including in-depth interviews with government officials (notably from the Tourism Office), tourism stakeholders, community members, and academics, along with field data analysis—this research identifies harmful behavioral patterns and proposes policy recommendations aimed at fostering harmony between tourism, society, and the environment. The findings highlight that education, stricter law enforcement, and enhanced collaboration among stakeholders are essential to cultivating a tourism experience that honors local values, strengthens communities, and safeguards natural resources. Ultimately, this study seeks to contribute to a new paradigm of tourism management—one that goes beyond economic gain to prioritize long-term social and environmental sustainability in Badung Regency as a premier travel destination.